Species identity of biocrust-forming lichens drives the response of soil nitrogen cycle to altered precipitation frequency and nitrogen amendment. (May 2016) - Liu, Yu-Rong; Delgado-Baquerizo, Manuel; Trivedi, Pankaj; He, Ji-Zheng; Singh, Brajesh K.
Abstract: Biological soil crusts (biocrusts) are fundamental components of drylands worldwide, and are of great importance for the regulation of ecosystem functioning. However, little is known on the role of species identify of biocrust-forming lichens in mediating the response of nitrogen (N) cycling to concurring global environmental change. Here, we conducted a microcosm study to evaluate how the species identity of biocrust-forming lichens ( Diploschistes thunbergianus, Psora crystallifera and Xanthoparmelia reptans ) regulate key processes of N cycling in response to simulated changes in rainfall frequency and N addition. We explicitly considered both direct and indirect effects (i.e. driven via microbial diversity and abundance) of global changes on N availability and losses using structural equation models. Our results showed that species of biocrust-forming lichens differentially mediated effects of N amendment and altered rainfall frequencies on belowground nitrate availability and N2 O flux rate. For instance, soils under P. crystallifera species showed the highest increase in nitrate content in response to N amendment under low rainfall frequency. Moreover, soils under D. thunbergianus showed the highest N2 O flux under high rainfall frequency without N addition. Interestingly, soils under X. reptans showed lowest and highest resistance in nitrate availability and N2 O flux, respectively, in response to N addition regardless of different rainfall frequencies. Strikingly, we only found an indirect impact of either rainfall frequency or N amendment on the nitrate availability (but not N2 O flux) driven via the ammonia-oxidizing community under X. reptans . Our results provide evidence that the species identity of biocrust-forming lichens modulates the response of N cycling to global change drivers. These findings have implications for predicting the potential consequence of altered rainfall patterns and environmental N inputs in dryland ecosystems. Highlights: Identify of biocrust species modulates response of N cycling to global change treatments. Resistance of N cycle processes to global change treatments is linked to identity of biocrust species. Impact of global change treatments on nitrate availability is mediated by soil microbial communities.